Fusion of Majorana bound states with mini-gate control in two-dimensional systems - Tong Zhou; Matthieu C. Dartiailh; Kasra Sardashti; Jong E. Han; Alex Matos-Abiague; Javad Shabani; Igor Žutić (Nature Communications, 2022)
The current efforts to look for Majorana bound states (MBS) still cannot probe the hallmark property, the non-Abelian statistics. Here, the authors propose to realize non-Abelian statistics through MBS fusion in mini-gate controlled planar Josephson junctions.